Habituating pain: Questioning pain and physical strain as inextricable conditions in the construction industry - Ajslev, Jeppe Z.N.; Lund, Henrik L.; Møller, Jeppe L.; Persson, Roger; Andersen, Lars L. (Nordic Journal of Working Life Studies, 2013)
In this article, we investigate the relations between discursive practices within the Danish construction industry and the perceived pain, physical deterioration, and strain affecting the construction workers. Of central importance is the widely accepted hegemonic discourse on physical strain and pain as unavoidable conditions in construction work. Based on 32 semi-structured interviews performed in eight case studies within four different construction professions, workers’ descriptions of physical strain and its relation to the organizational and social context are analyzed through concepts of subject positioning in discursive practice and a focus on power relations. The analysis shows that workers and employers reproduce certain types of traditional working class masculinities and search for high-pace productive working rhythms, which in combination with economic incentives common within the industry reproduce physical strain and the habituation of pain as unquestioned conditions in construction work. The understanding of this mutual reinforcement of the necessity of physically straining, painful, high-paced construction work provides fruitful perspectives on the overrepresentation of musculoskeletal deterioration within construction work and also sheds light on some of the difficulties in addressing and changing occupational health and safety practices in the construction industry.